2016
DOI: 10.1002/anie.201510681
|View full text |Cite
|
Sign up to set email alerts
|

Solid Molecular Phosphine Catalysts for Formic Acid Decomposition in the Biorefinery

Abstract: The co-production of formic acid during the conversion of cellulose to levulinic acid offers the possibility for on-site hydrogen production and reductive transformations. Phosphorus-based porous polymers loaded with Ru complexes exhibit high activity and selectivity in the base-free decomposition of formic acid to CO2 and H2 . A polymeric analogue of 1,2-bis(diphenylphosphino)ethane (DPPE) gave the best results in terms of performance and stability. Recycling tests revealed low levels of leaching and only a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
(35 reference statements)
1
36
0
Order By: Relevance
“…A series of catalysts based on P‐ and N‐donor‐containing polymers loaded with Ru and Ir was screened to assess the activity of the polymers in the aqueous hydrogenation of CO 2 to FA − . Catalysts were prepared by stirring the polymeric supports (pTPP, pDPPE, pTPPB, pTPrP, bpy‐CTF, CTF‐b; Figure ) with either [{Ru( p ‐cymene)Cl 2 } 2 ] or [{IrCp*Cl 2 } 2 ] in methanol, followed by filtration . Inductively coupled plasma optical emission spectroscopy (ICP‐OES) of the filtrate confirmed complete (>99 %) uptake in all cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of catalysts based on P‐ and N‐donor‐containing polymers loaded with Ru and Ir was screened to assess the activity of the polymers in the aqueous hydrogenation of CO 2 to FA − . Catalysts were prepared by stirring the polymeric supports (pTPP, pDPPE, pTPPB, pTPrP, bpy‐CTF, CTF‐b; Figure ) with either [{Ru( p ‐cymene)Cl 2 } 2 ] or [{IrCp*Cl 2 } 2 ] in methanol, followed by filtration . Inductively coupled plasma optical emission spectroscopy (ICP‐OES) of the filtrate confirmed complete (>99 %) uptake in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…The polymers pTPP and pDPPE (Figure ) were prepared as described previously . To study the effect of linker topology on the porosity and electronic structure, two additional polymers were synthesized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Previous studies indicated that PPh 3 can act as an electron-donor additive [35] and have a weak interaction with Ru 3+ ions, which can facilitate the decomposition of FA, thus being beneficial for the hydrogenation. [36] Therefore, the presence of PPh 3 is also crucially important for the reaction. Without PPh 3 , only 30 % yield of GVL could be produced from one-pot conversion of FF.…”
Section: Production Of Gvl From One-pot Conversion Of Ff Xylose and mentioning
confidence: 99%
“…No Ru leaching was detected after at urnover numbero f7 1000, which correspondst o2 0f ull cycles of full conversion. Palkovits et al [74] used porous phosphorous-based phenyl-polymers as the support in asimilar catalytic system. Their heterogeneous catalyst had an even higher activity for the dehydrogenation of aqueous dilute FA solutions.…”
Section: Catalytic Decomposition Of Bio-based Formic Acid Solutionsmentioning
confidence: 99%